2008
DOI: 10.1093/jee/101.5.1584
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Time Model for Predicting Adult Emergence of Western Corn Rootworm (Coleoptera: Chrysomelidae) in the Texas High Plains

Abstract: Field observations at three locations in the Texas High Plains were used to develop and validate a degree-day phenology model to predict the onset and proportional emergence of adult Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae) adults. Climatic data from the Texas High Plains Potential Evapotranspiration network were used with records of cumulative proportional adult emergence to determine the functional lower developmental temperature, optimum starting date, and the sum of degree-days fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…If a particular environment does not provide sufficient degree‐days for the complete development of a species it will be unlikely to persist. Degree‐days have been utilized extensively by pest managers in agricultural systems (Stevenson et al 2008) but to a lesser extent in the management of invasive insects. Nevertheless, work incorporating temperature and time dependent growth or degree‐day data on invasive ants has indicated the utility of this approach (Korzukhin et al 2001, Hartley and Lester 2003, Krushelnycky et al 2005).…”
mentioning
confidence: 99%
“…If a particular environment does not provide sufficient degree‐days for the complete development of a species it will be unlikely to persist. Degree‐days have been utilized extensively by pest managers in agricultural systems (Stevenson et al 2008) but to a lesser extent in the management of invasive insects. Nevertheless, work incorporating temperature and time dependent growth or degree‐day data on invasive ants has indicated the utility of this approach (Korzukhin et al 2001, Hartley and Lester 2003, Krushelnycky et al 2005).…”
mentioning
confidence: 99%
“…Ávila et al (2002) observed 449 SET DD based on the average daily soil temperature above 11.04°C at 0.10 m depth under maize canopy. Stevenson et al (2008) calculated the sum of degree-days for phenological events from the emergence onset to 99% adult WCR emergence. According to this model, the initial occurrence of WCR (1% occurrence) is expected after the air SET above 10°C and 600 DD.…”
Section: Resultsmentioning
confidence: 99%
“…Wilde (1971) determined the developmental threshold to be 11°C for eggs that were collected in Minnesota and 12.8°C for eggs that were collected in Kansas. Stevenson et al (2008) calculated the sum of WCR DD as 10°C. An upper threshold temperature (12.7°C) for WCR development was used (Diffenbaugh et al 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In total, 18, 13, and 15 data sets, each representing a different orchard location or sample year, were used to model A. nuxvorella moth ßight, oviposition, and Þrst observed nut entry, respectively. Stevenson et al (2008) reported that a modiÞed Gompertz function best Þt Diabrotica virgifera virgifera LeConte adult emergence patterns when compared with 18 other mathematical functions. Based upon this analysis, we chose a modiÞed Gompertz function to model capture of adult male A. nuxvorella in pheromone traps and oviposition activity as measured by cumulative proportional egg deposition on nutlets.…”
Section: Methodsmentioning
confidence: 99%
“…Prediction error of the bioÞx and frost-free models was calculated as the difference in days between the predicted and observed event (Stevenson et al 2008). Negative and positive values represent a model predicting events later and earlier than the observed event, respectively.…”
Section: Methodsmentioning
confidence: 99%